METHODOLOGY FOR TRANSLATING THICKNESS OF DEPOSITS INTO SEDIMENTATION RATE - Vladislav V. Drozdov; Tatyana V. Gnedkovskaya; Tatiana V. Voloshina; Ekaterina V. Storchak (Вестник Северо-Кавказского федерального университета)
The article deals with the formation of the geological structure in the central Caucasus in the Alpine geotectonic cycle, and offers a quantitative evaluation of the vibration movement mode.